Modeling the managed aquifer recharge for groundwater salinity management in the Sokh River Basin - Karimov, Akmal A.; Gracheva, I.; Miryusupov, F. (2010)
The vulnerability of surface water sources in the Syrdarya River Basin, due to their transboundary nature and climatic change, raises the importance of the shift from canal irrigation to conjunctive use of surface water and groundwater. However, groundwater development for irrigation may increase salinity of water due to leaching of dissolved solids from the salt-affected vadoze zone and blending of freshwater and saline water. In this paper managed aquifer recharge and discharge are analyzed as a strategy to maintain the groundwater quality of the Sokh aquifer of the Fergana Valley located upstream of the Syrdarya River Basin. Field studies suggested that groundwater recharge from the river floodplain may contribute to maintaining good-quality water in the groundwater system. The modeling study examines groundwater salinity change over a 5-year period under different managed groundwater recharge and discharge scenarios. The modeling results show that adopting water saving technologies and increased groundwater recharge through the river floodplain allows maintaining low groundwater salinity. The studies found that developing groundwater for irrigation increases salinity in the aquifer due to downward saline water fluxes. The results indicate that managed aquifer recharge and discharge contribute to maintaining salinity levels in the vadoze zone and groundwater.